A Song of Wind and Ice: Increased Frequency of Marine Cold‐Spells in Southwestern Patagonia and Their Possible Effects on Giant Kelp Forests. Issue 6 (2nd June 2022) - Mora‐Soto, A.; Aguirre, C.; Iriarte, J. L.; Palacios, M.; Macaya, E. C.; Macias‐Fauria, M.
Abstract: In contrast to other coastal regions of the world, the giant kelp ( Macrocystis pyrifera ) ecosystem in southwestern Patagonia has been persistent in area and associated biodiversity in the last decades. In this ecoregion, sea surface temperature (SST) records have consistently remained below the upper thermal threshold for kelp survival, however, no studies have analyzed the spatiotemporal variability of SSTs and their anomalies across the geographical diversity of the southwestern Patagonian coastline. We explored the geographical distribution of extreme warm and cold events in this region from latitudes 47°–56°S in a range of ∼1, 000 km, identifying the dates and spatial distribution of marine heatwaves (MHWs) and marine cold‐spells (MCSs) from 1982 to 2020. Results show that a peak in the number of MHWs occurred in the great El Niño year of 1998. Additionally, the 2014–2019 period has had more severe and extreme MCSs than the previous decades. We discuss the origin of these events with a focus on three main processes: (a) geographically constrained cold events caused by glacier melting, (b) regional cold events caused by extreme winds linked to the position of the polar front, and (c) extensive SST anomalies linked to planetary‐scale events such as El Niño and La Niña. Overall, those processes were conductive to counteract global warming trends locally/regionally, highlighting southwestern Patagonia as a possible climatic refugium for the giant kelp ecosystem. Despite this, the effects of freshwater inputs and storm turbulence on the exposed coasts facing the Southern Ocean may cause new kinds of stress on this ecosystem. Plain Language Summary: The western Patagonian coastline is habitat for one of the largest extents of the giant kelp ecosystem on the planet. The persistence of this ecosystem adapted to temperate‐to‐cold sea temperatures in this area may be explained by the absence of extreme marine heatwaves. In this research, we characterized the frequency, intensity, and duration of marine heatwaves (MHWs) and marine cold‐spells that occurred between 1982 and 2020, using information derived from satellites. These data provide sea surface temperatures for all the area of study. We confirmed that there were no extreme MHWs reaching stressing temperatures for giant kelp during the period we analyzed, which spans the longest continuous record available employing satellite data. Moreover, the last decade experienced extreme cold events in the coasts near the fjords and in the extreme south of the continent. In the current scenario of climate change, western Patagonia could be a climate refugium for giant kelp. We further identify glacier melt and increased turbulence in the sea due to increased storminess as emerging stressors of this ecosystem. Key Points: In Southwestern Patagonia, multiple extreme cold‐spells have occurred in the decade of 2010–2020 New potential stressors related to these extreme cold events include glacier meltwater and increased storm activity This research confirms observed trends of a cooling Southern Ocean, pointing out the need for studies at smaller scales in complex coastal areas